Periodicidad de solicitud y registro de estudios de laboratorio en el control del paciente diabético en una unidad de medicina familiar - Saldaña Otero, Gerardo (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
Type 2 diabetes mellitus (DM2) has become a public health problem, not only in Mexico but throughout the world. Their metabolic control is of the utmost importance, which is why it is important to know how often laboratory studies are requested that evaluate the control of the patient with DM2, in order to improve the quality of medical care provided to the beneficiary. Objective: Corroborate whether the frequency of laboratory studies in patients with DM2 in FMU 80 corresponds to the periodicity established in the CPG. Material and methods: Descriptive, transversal, retrospective study. We included 156 patients diagnosed with DM2 who attended an outpatient clinic of the Family Medicine Unit No. 80, from which the medical records from which the frequency data in the application and the registration of laboratory studies were obtained were reviewed. Compared with the provisions of NOM-015-SSA2-2010 and the CPG for the diagnosis, outpatient control goals and timely reference of prediabetes diabetes mellitus type 2 in adults at the first level of care 2013. The statistical analysis was performed by means of measures of central tendency, dispersion, and distribution by percentages and frequencies. Results: the periodicity of laboratory studies is not related to NOM-015-SSA2-2010 and CPG for diagnosis, outpatient control goals and timely reference of prediabetes diabetes mellitus type 2 in adults in the first level of care 2013. Conclusions: it was found that if there is a registry of laboratory studies, it is not related to the glycemic control of the patients. It is necessary to request HbA1c to establish an integral metabolic control of the patients.

La diabetes mellitus tipo 2 (DM2) se ha convertido en un problema de salud pública, no solo en México sino en todo el mundo. Su control metabólico es de suma importancia por lo cual es importante conocer con qué frecuencia se solicitan estudios de laboratorio que evalúan el control del paciente con DM2, para de esta manera mejorar la calidad de la atención médica que se proporciona al derechohabiente. Objetivo: Corroborar si la frecuencia de estudios de laboratorio en los pacientes con DM2 en la UMF 80 corresponde a la periodicidad establecida en la GPC. Material y métodos: Estudio descriptivo, transversal, retrospectivo. Se incluyeron 156 pacientes con diagnóstico de DM2 que acuden a consulta externa de la Unidad de Medicina Familiar No. 80 de los cuales se revisaron los expedientes clínicos electrónicos de donde se obtuvieron los datos de frecuencia en la solicitud y registro de estudios de laboratorio y se compararan con lo establecido en la NOM-015-SSA2-2010 y la GPC para el diagnóstico, metas de control ambulatorio y referencia oportuna de prediabetes diabetes mellitus tipo 2 en adultos en el primer nivel de atención 2013. El análisis estadístico se realizó por medio de medidas de tendencia central, dispersión, representado mediante porcentajes y frecuencias. Resultados: la periodicidad de estudios de laboratorio no guarda relación con la NOM-015-SSA2-2010 y GPC para el diagnóstico, metas de control ambulatorio y referencia oportuna de prediabetes diabetes mellitus tipo 2 en adultos en el primer nivel de atención 2013. Conclusiones: se encontró que si existe registro de estudios de laboratorio sin embargo no guarda relación con el control glucémico de los pacientes. Hace falta solicitar HbA1c para establecer un control metabólico integral de los pacientes.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4311; info:eu-repo/classification/cti/3; FCMB-E-2019-0020; Estudios de laboratorio; Diabetes mellitus tipo 2; Primer nivel de atención